Human Resource Improvement Strategies, Impact of Organizational Culture on Performance - Maulana, Moh. Jaya (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2022)
Companies must create a strategy that is able to build employee awareness of their potential and abilities in the form of aspirational insights and ethics as a work culture. So with this the purpose of this research is to find out the strategy in improving the performance of human resources through organizational culture at PT Cipta Arkun Mandiri. To answer the research objectives, it was designed using a descriptive method with a qualitative approach. The data collection technique used is the analysis of observation, interviews and documentation. This study uses 2 kinds of methods, namely SWOT analysis and Balanced Scorecard, the unit of analysis in this study is informants who become informants, namely the leadership, employees and customers of PT Cipta Arkun Mandiri. Sampling of data sources was carried out purposive and snowball. The results of this analysis are to optimize performance with job training seeking to empower existing human resources by motivating, because system and management changes will change the corporate culture in order to build work effectiveness.